The humus state ferralitic soil ecosystems in the high land of Vietnam - Nguyen Van Duc, -; Lareshin, V G; Slobodyanuk, K V (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii︠a︡ agronomii︠a︡ i zhivotnovodstvo, 2013)
On bases of an analysis of the actual materials and important questions on the significant issues as a part of a problem of knowledge of the nature and receptions of regulation of a condition of organic matter and a humus in soils of various landscapes of Vietnam.